The prognostic value of prognostic nutritional index in postoperative onset of PAH in children with isolated VSD: a prospective cohort study based on propensity score matching analysis - Zhang, Zeying; Su, Jing; Li, Chenyang; Cao, Shirui; Sun, Chao; Lin, Qiuzhen; Luo, Haiyan; Xiao, Zhenghui; Xiao, Yunbin; Liu, Qiming (Frontiers in Pediatrics, 2024)
The mechanism of pulmonary arterial hypertension (PAH) after surgery/intervention for isolated venticlular septal defect (VSD) in children is unknown. Reliable prognostic indicators for predicting postoperative PAH are urgently needed. Prognostic nutration index (PNI) is widely used to predict postoperative complications and survival in adults, but it is unclear whether it can be used as an indicator of prognosis in children.Children's Hospital from 2020 to 2023 were collected. A 1:1 propensity score matching (PSM) analysis was performed using the nearest neighbor method with a caliper size of 0.2 Logistics regression analysis is used to examine factors associated with the development of PAH.The cut-off value for PNI was determined as 58.0. After 1:1 PSM analysis, 49 patients in the low PNI group were matched with high PNI group. Children in the low PNI group had higher risk of postoperative PAH (P = 0.002) than those in the high PNI group. Multivariate logistics regression analysis showed that PNI (RR: 0.903, 95%CI: 0.816-0.999, P = 0.049) and tricuspid regurgitation velocity (RR: 4.743, 95%CI: 1.131-19.897, P = 0.033) were independent prognostic factors for the development of PAH.PNI can be used as a prognostic indicator for PAH development after surgery/intervention in children with isolated VSD.